Fast-Track Long Term Continuous Heart Monitoring in a Stroke Clinic: A Feasibility Study - Khan, Ayesha; Abedi, Vida; Ishaq, Farhan; Sadighi, Alireza; Adibuzzaman, Mohammad; Matsumura, Martin; Holland, Neil; Zand, Ramin (Frontiers in Neurology, 2020)
Background: Paroxysmal atrial fibrillation (PAF) or flutter is prevalent among patients with cryptogenic stroke. The goal of this study was to investigate the feasibility of incorporating a fast-track, long term continuous heart monitoring (LTCM) program within a stroke clinic. Method: We designed and implemented a fast-track LTCM program in our stroke clinics. The instrument that we used for the study was the ZioXT® device from IRhythm™ Technologies. To implement the program, all clinic support staff received training on the skin preparation and proper placement of the device. We prospectively followed every patient who had a request from one of our inpatient or outpatient stroke or neurology providers to receive LTCM. We recorded patients’ demographics, the LTCM indication, as well as related quality measures including same-visit placement, wearing time, analyzable time, LTCM application to the preliminary finding time, as well as patients’ out of pocket cost. Results: Out of 501 patients included in the study, 467 (93.2%) patients (mean age 65.913; men: 48%) received LTCM; and 92.5% of the patients had the diagnosis of stroke or TIA. 93.7% of patients received their LTCM during the same outpatient visit in the stroke clinic. The mean wearing time for LTCM was 12.1 days (out of 14 days). The average analyzable time among our patients was 95.0%. Eighteen (3.9%, 95%CI: 2.4-6.0) patients had at least one episode of PAF that was sustained for more than 30 seconds. The rate of PAF was 5.9% (95% CI: 3.5-9.2) among patients with the diagnosis of stroke. Out of 467 patients, 392 (84%) had an out-of-pocket cost of less than $100. Conclusion: It is feasible to implement a fast-track cardiac monitoring as part of a stroke clinic with proper training of stroke providers, clinic staff, and support from a cardiology team.